Community Health Services for Geriatrics and Widows South–South Nigeria - Akpalaba, I. O.; Blackie, F. F.; Akpalaba, R. U. E. (Emerging Trends in Disease and Health Research Vol. 2, 2022)
Introduction: Geriatrics and widows are neglected in the society. The geriatrics age groups are seen as unproductive. Widows, on the other hand, are humiliated traditionally by their husbands’ family members and community. They face surmounting problems which shadow their urge to seek medical attention. Aim: To determine the burden of Ear, Nose and Throat (ENT) and medical diseases in Geriatrics and Widows through identification of common ENT and medical conditions in them. Objectives: To identify the ear diseases among geriatrics at the Dagomo foundation home for the elderly. To identify the ear diseases among widows in Ubiaja community. To identify the medical conditions among the widows in Ubiaja community. Methods: This study was a 7months prospective study from September, 2017 to April, 2018. The study centers were Dagomo foundation home for the elderly in Benin City and St. Benedict Catholic Church, Ubiaja in Edo central. Total population sampling technique was used. All the elderly and widows who gave consent to the study constituted the sample size. Health talk was given; history taking, Ear, Nose, Throat and general body examinations were done. Data on the disease burden identified were recorded. Those that needed further evaluation and management were referred accordingly. Data was statistically analyzed with SPSS Version 20. P value < 0.05 was considered statistically significant. Results: 50 geriatrics and 67 widows participated. The age range was from 60 – 90 years (mean age of 69.50±7.78years) and 36 – 85years (mean age of 59.61±9.36) for Geriatrics and widows respectively. Among the geriatrics were 13 males and 37 females while widows were 67. Seventeen (17) different ENT diseases were identified in Geriatrics while 7 ENT conditions and 12 medical conditions were identified in the widows. Predominant ENT diseases were Otitis Media with Effusion (34.9%), Left Cerumen Auris and Otomycosis in similar proportion (20.9%) in Geriatrics. Right Cerumen Auris predominated in widows (65.6%) followed by Left Cerumen auris (50.0%) and Otitis Externa (28.1%). Osteoarthritis was the commonest medical condition (90.6%) in widows. Tests of association were not statistically significant. Conclusion: There is significant burden of Ear, Nose, Throat and medical diseases in the Geriatrics and widows. Recommendations: Government should plan specialist healthcare measures to improve the quality of life of geriatrics and widows. Government should ensure an educational policy to develop age-appropriate training protocols for children and young adults on the challenges associated with aging.